P023 Tenosynovitis and HLA-SE predict arthritis onset in ACPA-positive individuals at risk of developing rheumatoid arthritis. (March 2019) - Hensvold, AH; Kisten, Y; Hansson, M; Cîrciumaru, A; Sun, M; Fei, G; af Klint, E; Rezaei, H; Antovic, A; Catrina, AI
Abstract : Career situation of first and presenting author: Post-doctoral fellow Introduction: Anti-citrullinated protein antibodies (ACPA) are predictive markers with pathological effects in rheumatoid arthritis (RA). Previous prospective studies have used a clinical definition of arthritis. Thus, we aimed to investigate risk factors of developing arthritis in ACPA-positive subjects with musculoskeletal complaints who did not have any of clinical and ultrasound signs of arthritis. Methods: Subjects with positive ACPA-test referred from primary care to rheumatology clinic, lacking arthritis in hands and feet by clinical and ultrasound examination (according to EULAR-OMERACT synovitis definition), were recruited into the Risk-RA research program. Patient included between years 2015–2016 with clinical data up to 2017 were analysed. Blood samples from inclusion were analysed for 13 specific ACPA reactivities using a custom made ImmunoCAP ISAC microarray. Presences of HLA-SE risk gene were analysed using DR low-resolution kit. Results: 41% (27 out of 66) of the Risk RA subjects developed arthritis during a median follow up of 8 months. The rest was followed 25 months in median without any signs of arthritis. Subjects developing arthritis tended to have a higher concentration of anti-CCP, more tender joints and rheumatoid factor positivity at inclusion compared to those not developing arthritis. The number of ACPA-reactivities (mean 6 vs 3), the presence of HLA-SE (89% vs 56%) and the occurrence of ultrasound detected tenosynovitis (44% vs 5%) at inclusion were significantly increased in subjects developing arthritis compared to those not developing arthritis. Univariate cox proportional hazards regression showed a hazard ratio (HR) for arthritis development of 1.1 for every increase in number of ACPA reactivities (95% CI 0.99 to 1.2, p 0.07); HR: 4.4 (95% CI 2.0 to 9.5, p 0.0002) for tenosynovitis and for HR: 4.9 (95% CI 1.5 to 16, p 0.01) for HLA-SE carriers. All subjects with tenosynovitis (n=14) prior to arthritis development were carriers of HLA-SE, except for one subject but similar to the majority this HLA-SE no-carrier also progressed to arthritis. Conclusions: Subjects with ACPA-positive musculoskeletal complaints lacking any clinical and ultrasound signs of arthritis are at high risk of developing arthritis, especially carriers of HLA-SE with tenosynovitis. The role of inflammatory spreading from tendons (synovial sheath) to synovial tissue within joints need to be further investigated. Disclosure of Interest: None declared